Potentially inappropriate medicines in a cohort of community‐dwelling older people in New Zealand. Issue 1 (26th March 2013) - Nishtala, Prasad S; Bagge, Michael L; Campbell, A John; Tordoff, June M
<x xml:space="preserve">Abstract</x> Aim To examine independent factors associated with potentially inappropriate medicines (PIM) among 316 community‐dwelling people aged ≥75 years living in Dunedin. Methods People aged ≥75 years living in the community in Dunedin, New Zealand, taking ≥1 prescription medicines, randomly sampled from the electoral roll, were interviewed about their medicine‐taking practices. A medication inventory comprising prescription and non‐prescription medicines was taken from each participant at the time of the interview. Participants used a median of seven prescription medicines (range 1–19) and one non‐prescription medicine (0–14). PIM were identified using the updated 2012 Beers criteria. Results PIM were identified in 42.7% (n = 135) older people. A total of 23 (7.2%) took two PIM, five (1.5%) took three PIM, four (1.2%) took four PIM and one (0.3%) took five PIM. Of the 184 total PIM identified, the top three drug classes were non‐COX‐selective non‐steroidal anti‐inflammatory drugs (24.0%), tricyclic antidepressants (16.8%) and benzodiazepines (14.6%). Polypharmacy (adjusted odds ratio [OR] 2.06, 95% confidence interval [CI] 1.03–4.12) and the use of any psychotropic drug use (OR 22.05, 95% CI 5.80–83.84) were associated with PIM exposure. In the Poisson regression model, the risk of taking a PIM significantly decreased with age (OR 0.95, CI 0.91–0.99) and increased as the number of drugs prescribed increased (OR 1.11, CI 1.08–1.15). Conclusion The prevalence of PIM is relatively high in community‐dwelling older people aged ≥75 years living in New Zealand. PIM defined by the Beers criteria might be a useful initial screening tool, before efforts to stop unsafe medication use or replace with safer alternatives are initiated. Geriatr Gerontol Int 2014; 14: 89–93.